Preaching between affirmation and anticipation: contours of a paradoxical homiletic - Cilliers, Johan (Stellenbosch Theological Journal, 2016)
Taking the many paradoxes that the South African society is currently facing as point of departure, this article sets out by defining the notion of paradox, followed by the drawing of a few contours of a homiletic that endeavours to preach the promises of God within, and against, these paradoxes. Four movements are identified in this process, namely preaching as affirmation, provocation, migration, and anticipation. The article ends with a reflection on a well-known artwork by former South African president, Nelson Mandela.